Ground Penetrating Radar Survey Across The Bok Bak Fault, Kedah, Malaysia - Ulfa, Yuaniarti; Jamel, Nur Fathin Mohd; Samsuardi, Mardiana (BRIN Publishing, 2013)
A ground penetrating radar (GPR) survey was done across the Bok Bak Fault zone in Baling, Kedah in order to investigate the shallow subsurface geology of the Bok Bak fault zone, its extension and associated weak zones within the study area. GPR data acquisition was compared with visual inspection on the slope of the outcrop. Ten GPR profiles were acquired using 250 MHz GPR frequency. Basic data processing and filtering to reduce some noise and unwanted signal was done using MALA RAMAC Ground Vision software. The data penetrate around 2 meters in depth for all survey lines. In most lines shows clear images of shallowest Bok Bak Fault (NW trending) as detected at distance of 28 m horizontal marker. It also exhibits several sets of faults as a result of Bok Bak Fault deformation, including the conjugate NE trending fault (Lubok Merbau Fault). Active seismicity encompasses the Malay-Thai Peninsular trigger the changes of Bok Bak Fault dipping direction, steeper dips of conjugate faults and faults or fractures rotational movement.